PROTOCOLS FOR MENTAL HEALTH CARE IN PRIMARY-LEVEL SERVICES: SUBSIDIES FOR TRANSFORMING THE ASSISTANCE PROVIDED - Cordeiro, Gisele Fernandes Tarma; dos Santos, Tatiana Marques; Ferreira, Rosa Gomes dos Santos; Guljor, Ana Paula Freitas; Peters, Angela Aparecida; Peres, Maria Angélica de Almeida (Cogitare Enfermagem, 2022)
Objective: to analyze the repercussions on mental health care due to the implementation of Care Conduct Protocols in a Basic Health Unit from Juiz de Fora (Minas Gerais – Brazil). Method: a historical-social study carried out in 2018, having as direct sources written documents and oral testimonies analyzed according to the assumptions of the Psychiatric Reform. Results: the following categories are presented: a) Reorganization of mental health care through the implementation of Conduct Protocols; b) Referral and counter-referral process between Basic Health Units and specialized mental health care services; and c) Transformation of mental health care. Conclusion: the protocols organized the mental health care network, supporting multiprofessional training, introducing Primary Health Care as a gateway to welcoming, treatment and monitoring in territorial mental health.